On Regimes and the Political Outcomes : A Comparative case study between Indonesia and Thailand - Ratthanawin, Supachok (Political Science Critique, 2022)
This research aims to study how regimes have impacts on political results, by focusing on Indonesia and comparing the findings with that of Thailand. The research shows the differences in political structures between these two countries which affect their political outcomes in several levels, ranging from constitutions, to election systems, and to local administrations. Differences in political structures play an important role in establishing a stable democracy. If we can understand the conditions of each society, and adapt to meet those conditions, It can help establish a strong democracy.